Green synthesized Ag–Cu nanocomposites as an improved strategy to fight multidrug-resistant bacteria by inhibition of biofilm formation: In vitro and in silico assessment study - Abbas Jafar Abdulkareem; Hasoon Buthenia Abd Alhamza; Jabir Majid Sakhi; Ghotekar Suresh; Swelum Ayman Abdel-Aziz (Green Processing and Synthesis)
This study explores the green synthesis and characterization of monometallic Ag nanoparticles (NPs), Cu NPs, and bimetallic Ag–Cu NPs mediated by the aqueous extract of Syzygium aromaticum as a reducing agent. It aims to address the growing problem of antibiotic-resistant bacterial infections, particularly those caused by Escherichia coli and Staphylococcus saprophyticus. The synthesized NPs were characterized using techniques such as UV-Vis, X-ray diffraction, and transmission electron microscopy, and their antimicrobial, antibiofilm, and ROS production activities were evaluated. Results revealed that bimetallic Ag–Cu NPs exhibited higher antibacterial and antibiofilm effects than monometallic counterparts, with enhanced synergistic effects when combined with antibiotics. Because of the importance of Ag NPs and Cu NPs, the application of molecular docking simulations to Ag NPs and Cu NPs can provide comprehensive insights into their chemical and biological properties. This technique collectively aids in assessing the viability of Ag NPs and Cu NPs as drug candidates, optimizing their structures for better efficacy and safety, and predicting their behavior within biological systems. The study concludes that Ag–Cu NPs hold promise for addressing resistant bacterial strains and biofilm-related infections.